Assessment of Nutritional Status of Under Five Years Children in Kolati Bhumlu of Kavrepalanchok District - KC, Amita; Bohara, Ranendra (Journal of Advanced Academic Research, 2023)
Background: The nutritional status of children is one of the major indicators of child survival and a proxy indicator for the general health of the population. Malnutrition is a significant public health issue in the majority of developing nations and is particularly prevalent among children under five years of age. Mortality and morbidity among children under-five years of age are influence by nutritional status. The context of Nepal, more than one-third (36%) of children under-five years of age stunted or too short for their age. 10% of children wasted (too thin for height), a sign of acute malnutrition. 27% of children underweight or too thin for their age. These children had greater risk of severe acute malnutrition and death.Objective: Study’s objective was to assess the nutritional status of under-five year’s children and factors associated with malnutrition.Method: A descriptive cross-sectional study conducted in Kolati Bhumlu of Kavrepalanchok district of Nepal. A total of 115 under-five year’schildren and their mothers were included in study. Statistical Package for the Social Sciences (SPSS) version16 was used to analyze the data.Result: The prevalence of underweight was found to be 28.7% according to the classification of malnutrition based on Z- score .Similarly, the prevalence of wasting was found to be 18.3% and the prevalence of stunting was found to be 29.6%. According to Gomez’s malnutrition classification (NCHS/WHO as standard) for Weight for age (underweight) 3.5% children were severely malnourished. According to Water-low’s classification, regarding the height for age (stunting) 9.6% children were severely malnourished. Regarding MUAC measurement 7.8% children had severe malnutrition. The Gender of the child was associated with stunting.Conclusion: In the study population, the high prevalence of malnutrition especially stunting among under-five years children. Taking weight, height, age, and mid- upper arm circumference (MUAC) measurements of malnourished children more than three-fifths of them were below -2SD and nearly one-fourths were below -3SD which needs intervention.